2012
DOI: 10.2166/nh.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Scale issues for assessment of nutrient leaching from agricultural land in Latvia

Abstract: This paper deals with water quality assessment and recommendations for a classification system based on nitrogen (N) and phosphorus (P) concentrations. In order to evaluate the influence of agricultural intensity, climate and hydrology on water quality, the long-term data (from 1995 to 2009) collected in three Latvian diffuse pollution monitoring sites (Berze, Mellupite and Vienziemite) were analysed. Measurements were carried out within areas where agriculture was the main source of diffuse nutrient loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Hansen et al, 2001;Rode et al, 2009Rode et al, , 2010. It was reported that the nutrient concentrations in the streams were highly correlated with the percentage of agricultural land (Lagzdins et al, 2012). Through influencing runoff generation and nutrient turnover processes, climate variability (precipitation and temperature) affects nitrate leaching (Andersen et al, 2006;Bouraoui et al, 2004;De Klein and Koelmans, 2011;Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hansen et al, 2001;Rode et al, 2009Rode et al, , 2010. It was reported that the nutrient concentrations in the streams were highly correlated with the percentage of agricultural land (Lagzdins et al, 2012). Through influencing runoff generation and nutrient turnover processes, climate variability (precipitation and temperature) affects nitrate leaching (Andersen et al, 2006;Bouraoui et al, 2004;De Klein and Koelmans, 2011;Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [9,[50][51][52] determined that with the increase in catchment area, the soluble nitrogen concentrations in the stream water runoff decreased. They explained the phenomenon by the higher impact of ground water discharge in the large catchments.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by HELCOM [5,6], agriculture contributes approximately 80% of the total nitrogen load entering the Baltic Sea. Long-term observations in the Baltic countries (Estonia, Latvia and Lithuania) indicate that average annual losses of total nitrogen and total phosphorus from agricultural catchments can vary from 5 to 40 kg N ha −1 [7][8][9][10] and from 0.120 to 0.421 kg P ha −1 [11], respectively. These amounts were highly affected by various factors.…”
Section: Introductionmentioning
confidence: 99%
“…Fölster et al 2012;Hauken et al 2012), or in some cases in scientific journals for single countries (e.g. Gaigalis & Račkauskaitė 2001;Vuorenmaa et al 2002;Sileika et al 2005;Kyllmar et al 2006;Bechmann et al 2008;Lagzdins et al 2012) or single streams (e.g. Mander et al 2000;Bechmann & Stålnacke 2005), but mostly with different chemical parameters, time periods assessed or various statistical methods.…”
Section: Introductionmentioning
confidence: 99%